Palladium-doped tin dioxide sensitive material and preparation method thereof, double-layer membrane structure gas sensor and preparation method and application thereof
By combining palladium-doped tin dioxide sensitive material with Na-type X molecular sieve layer, a double-layer film structure gas sensor is formed, which solves the problem of poor stability of traditional hydrogen sensors in high humidity environments, and achieves high sensitivity and long-term stability. Hydrogen detection effect.
Patent Information
- Application Number
- CN202411333166.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2024-12-31
AI Technical Summary
Traditional hydrogen sensors have poor stability and low sensitivity in high humidity environments, which cannot meet the needs of actual engineering applications.
Palladium-doped tin dioxide sensitive material is prepared by mixing SnO2 gel, palladium source and reducing agent for reduction treatment, and combined with Na-type X molecular sieve layer to form a double-layer film Structured gas sensors to enhance moisture resistance and high temperature stability.
High sensitivity hydrogen detection is achieved, and long-term stability is maintained under high humidity and high temperature conditions, which significantly improves the detection performance of the sensor.
Smart Images

Figure CN119224070A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of gas sensors, and in particular relates to a palladium-doped tin dioxide sensitive material and a preparation method thereof, a double-layer membrane structure gas sensor and a preparation method and application thereof. Background Art
[0002] As a clean energy, hydrogen has received more and more attention and importance. Its high energy density, zero emissions and renewable characteristics make it an important choice to replace traditional fossil energy. However, with the development of hydrogen energy technology, the safety issue of hydrogen has become increasingly prominent. Hydrogen is flammable and explosive. Once it leaks or the concentration exceeds the safe range, it is likely to cause serious safety accidents. Therefore, rapid and accurate detection of hydrogen concentration has become a top priority.
[0003] Traditional hydrogen sensors mainly include metal oxide semiconductor gas sensors, electrochemical sensors, etc. Although these sensors can meet the needs of hydrogen detection to a certain extent, they have the defect of low sensitivity; and traditional hydrogen sensors have the defect of poor stability in harsh environments with high humidity (50-90% RH), and the application effect is not good, which cannot meet the needs of actual engineering applications. Summary of the invention
[0004] The purpose of the present invention is to provide a palladium-doped tin dioxide sensitive material and a preparation method thereof, a double-layer membrane structure gas sensor and a preparation method and application thereof. The gas sensor prepared using the palladium-doped tin dioxide sensitive material of the present invention has high sensitivity and excellent high temperature resistance and high humidity resistance stability.
[0005] In order to achieve the purpose of the present invention, the present invention provides the following technical solutions:
[0006] A method for preparing a palladium-doped tin dioxide sensitive material comprises the following steps:
[0007] The SnO2 gel, the palladium source and the reducing agent are mixed and subjected to reduction treatment to obtain the palladium-doped tin dioxide sensitive material.
[0008] Preferably, the method for preparing the SnO2 gel comprises the following steps:
[0009] Providing a SnO2 precursor solution, wherein the SnO2 precursor solution comprises a tin source, an alkali source and water; the pH value of the SnO2 precursor solution is 9 to 11;
[0010] The SnO2 precursor solution is subjected to hydrothermal treatment to obtain the SnO2 gel.
[0011] Preferably, the tin source comprises one or more of tin salts, tin oxides and tin hydroxides;
[0012] The alkaline source includes one or more of a weak acid and weak base salt, a strong base and a weak base.
[0013] Preferably, the palladium source includes one or more of palladium salts, palladium oxides and palladium hydroxide.
[0014] Preferably, the mass ratio of the tin source to the alkali source is 1-5:1-3;
[0015] The mass ratio of the tin source, the palladium source and the reducing agent is 100-500:1-3:1-5.
[0016] Preferably, the reduction treatment is carried out at a temperature of 5 to 50° C. for a time of 1 to 5 hours; and the reduction treatment is carried out under ultraviolet light conditions.
[0017] The present invention also provides a palladium-doped tin dioxide sensitive material prepared by the preparation method described in the above technical solution, comprising tin dioxide and palladium particles doped on the surface of the tin dioxide.
[0018] The present invention also provides a double-layer membrane structure gas sensor, comprising a substrate, a test electrode is arranged on one side of the substrate, and a heating electrode and a heating plate are sequentially stacked on the other side of the substrate; a palladium-doped tin dioxide sensitive material layer and a Na-type X molecular sieve covering layer are sequentially stacked on the surface of the test electrode and the surface of the substrate not covered by the test electrode; the palladium-doped tin dioxide sensitive material layer is formed by the palladium-doped tin dioxide sensitive material described in the above technical solution.
[0019] The present invention also provides a method for preparing the double-layer membrane structure gas sensor described in the above technical solution, comprising the following steps:
[0020] A test electrode is arranged on one side of the substrate, and a heating electrode and a heating plate are sequentially stacked on the other side;
[0021] Applying a palladium-doped tin dioxide sensitive material dispersion to the test electrode and an uncovered area on the side of the substrate where the test electrode is provided, to obtain a palladium-doped tin dioxide sensitive material layer on the surface of the substrate and the test electrode;
[0022] The Na-type X molecular sieve dispersion is printed onto the surface of the palladium-doped tin dioxide sensitive material layer, and the double-layer membrane structure gas sensor is obtained after aging.
[0023] The present invention also provides the application of the double-layer membrane structure gas sensor described in the above technical solution or the double-layer membrane structure gas sensor prepared by the preparation method described in the above technical solution in H2 or CO detection.
[0024] The invention provides a method for preparing a palladium-doped tin dioxide sensitive material, comprising the following steps: mixing SnO2 gel, a palladium source and a reducing agent, and performing a reduction treatment to obtain the palladium-doped tin dioxide sensitive material. The invention adopts a sol-gel method to prepare a palladium-doped tin dioxide (Pd@SnO2) nanoparticle sensitive material, and the catalytic effect of the Pd nanoparticles increases the adsorption of oxygen (O 2-ads ) concentration, which reduces the activation energy of the gas-sensitive reaction and promotes the adsorption of oxygen (O 2-ads ) reacts with H2 and has high sensitivity. The material has a porous structure and a large specific surface area, which is conducive to gas diffusion and can achieve rapid adsorption and desorption of gas. When used in gas detection, it can achieve high-sensitivity detection and a fast response speed.
[0025] The present invention also provides a double-layer membrane structure gas sensor, wherein the Na-type X molecular sieve covering layer can block water vapor molecules in the environment, reduce the interference of water vapor molecules on the Pd@SnO2 sensitive material layer and the gas-sensitive reaction, and enhance the moisture resistance and long-term stability of the Pd@SnO2 sensitive material layer against high temperatures. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0027] Figure 1 Schematic diagram of the structure of the double-layer membrane structure gas sensor obtained in Example 1 of the present invention, wherein the double-layer membrane structure gas sensor substrate is used as a reference, (a) is a schematic diagram of the upper surface structure of the double-layer membrane structure gas sensor substrate, including a substrate 1, a test electrode 2, a platinum wire 3, a Pd@SnO2 sensitive material layer 4, and a Na-type X molecular sieve covering layer 5; (b) is a schematic diagram of the lower surface structure of the double-layer membrane structure gas sensor substrate, including a heating electrode 6 and a heating plate 7;
[0028] Figure 2 The SEM images of the Pd@SnO2 sensitive material obtained in Example 1 of the present invention, wherein (a) is the SEM image of the Pd@SnO2 sensitive material when the size is 2 μm; (b) is the SEM image of the Pd@SnO2 sensitive material when the size is 1 μm;
[0029] Figure 3 The XRD spectra of the Pd@SnO2 sensitive material and the Na-type X molecular sieve obtained in Example 1 of the present invention; wherein (a) is the XRD spectrum of the Pd@SnO2 sensitive material, and (b) is the XRD spectrum of the Na-type X molecular sieve;
[0030] Figure 4 The response sensitivity curves of the gas sensors obtained in Example 1 and Comparative Examples 1 to 2 of the present invention under different temperature conditions are shown;
[0031] Figure 5 The graphs are the response resistance curves of the gas sensors obtained in Example 1 and Comparative Example 1 of the present invention to different concentrations of H2;
[0032] Figure 6 The response sensitivity curves of the gas sensors obtained in Example 1 and Comparative Example 1 of the present invention under different H2 concentration conditions;
[0033] Figure 7 This is a graph showing the resistance change between the gold electrodes of the gas sensor obtained in Example 1 of the present invention after six cycles of testing 300ppm H2 gas;
[0034] Figure 8 The response sensitivity curves of the gas sensors obtained in Example 1 and Comparative Example 2 of the present invention under different humidity conditions are shown;
[0035] Fig. 9 This is a stability test curve of the gas sensor obtained in Example 1 of the present invention to 300 ppm H2 at 253°C. DETAILED DESCRIPTION
[0036] The present invention provides a method for preparing a palladium-doped tin dioxide sensitive material, comprising the following steps:
[0037] The SnO2 gel, the palladium source and the reducing agent are mixed and subjected to reduction treatment to obtain the palladium-doped tin dioxide sensitive material.
[0038] In the present invention, unless otherwise specified, all preparation raw materials are preferably commercially available products well known to those skilled in the art.
[0039] In the present invention, the method for preparing the SnO2 gel preferably comprises the following steps:
[0040] Providing a SnO2 precursor solution, wherein the SnO2 precursor solution comprises a tin source, an alkali source and water, and the pH value of the SnO2 precursor solution is 9 to 11;
[0041] The SnO2 precursor solution is subjected to hydrothermal treatment to obtain the SnO2 gel.
[0042] In the present invention, the tin source preferably includes one or more of tin salts, tin oxides and tin hydroxides, more preferably tin salts; the tin salt is preferably hydrochloride, nitrate or sulfate, more preferably hydrochloride, further preferably SnCl4 or SnCl2; the alkali source preferably includes one or more of weak base weak acid salts, strong bases and weak bases; the weak base weak acid salt is preferably NH4HCO3; the strong base is preferably NH3·H2O; the water is preferably deionized water; the solid-liquid ratio of the tin source and water is preferably 0.5-2.5g:10-30mL, more preferably 0.8-1.5g:15-25mL; the solid-liquid ratio of the alkali source and water is preferably 0.5-1.5g:100-150mL, more preferably 0.8-1.3g:100-150mL; the mass ratio of the tin source and the alkali source is preferably 1-5:1-3, more preferably 1:1.2-2. In the present invention, the pH value of the SnO2 precursor solution is preferably 9-11. More preferably, it is 10 to 10.5; if the pH value of the SnO2 precursor solution of the present invention does not meet the above requirements, it is also preferred to adjust the pH of the SnO2 precursor solution; the reagent for adjusting the pH value of the SnO2 precursor solution is preferably one or more of ammonia water, NaOH and KOH, more preferably ammonia water; the concentration of the ammonia water is preferably 20 to 50%, more preferably 28 to 30%. The present invention mixes a tin source, an alkali source and water, and performs a double decomposition reaction to obtain a SnO2 precursor solution; the double decomposition reaction is preferably carried out at room temperature and under stirring conditions. The present invention also preferably centrifuges the product obtained by the double decomposition reaction, collects the liquid product, and obtains a SnO2 precursor solution; the number of centrifugations is preferably 4 to 6 times, more preferably 4 to 5 times.
[0043] In the present invention, the SnO2 precursor solution and water are preferably mixed before adjusting the pH value of the SnO2 precursor solution; the mass ratio of the SnO2 precursor solution to water is preferably 1:10 to 30, and more preferably 1:15 to 20.
[0044] In the present invention, the temperature of the hydrothermal treatment is preferably 100-250°C, more preferably 200-250°C; the time is preferably 2-5h, more preferably 3-4h; the hydrothermal treatment is preferably carried out in a stainless steel autoclave lined with polytetrafluoroethylene.
[0045] After obtaining the SnO2 gel, the present invention mixes the SnO2 gel, a palladium source and a reducing agent, performs a reduction treatment, and obtains the palladium-doped tin dioxide sensitive material. In the present invention, the palladium source preferably includes one or more of a palladium salt, a palladium oxide and palladium hydroxide, and the palladium salt is preferably a hydrochloride, a nitrate or a sulfate, more preferably a hydrochloride, and further preferably PdCl2 or Pd(NO3)2; the reducing agent preferably includes sodium borohydride or hydrazine hydrate; the mass ratio of the tin source, the palladium source and the reducing agent is preferably 100-500:1-3:1-5, more preferably 200-350:1:1; the temperature of the reduction treatment is preferably 5-50°C, more preferably 10-30°C; the time is preferably 1-5h, more preferably 2-3h; the reduction treatment is preferably carried out under ultraviolet light conditions.
[0046] In the present invention, it is preferred to firstly mix the SnO2 gel and the palladium source to obtain a mixed system; then mix the mixed system with a reducing agent to perform a reduction treatment; the first mixing is preferably performed under stirring conditions; the first mixing time is preferably 0.5 to 1 hour. In the present invention, the SnO2 gel is also preferably dispersed before use; the dispersion is preferably ultrasonic dispersion, and the dispersion time is preferably 10 to 20 minutes.
[0047] In the present invention, after the reduction treatment, the obtained reduction product is preferably centrifuged, and the solid product after centrifugation is washed and dried in sequence; the number of centrifugation is preferably 4 to 6 times, more preferably 4 to 5 times; and the drying is preferably freeze-drying.
[0048] The present invention also provides a palladium-doped tin dioxide sensitive material prepared by the preparation method described in the above technical solution, comprising tin dioxide and palladium particles doped on the surface of the tin dioxide.
[0049] The present invention also provides a double-layer membrane structure gas sensor, comprising a substrate, a test electrode is arranged on one side of the substrate, and a heating electrode and a heating plate are sequentially stacked on the other side of the substrate; a palladium-doped tin dioxide sensitive material layer and a Na-type X molecular sieve covering layer are sequentially stacked on the surface of the test electrode and the surface of the substrate not covered by the test electrode; the palladium-doped tin dioxide sensitive material layer is formed by the palladium-doped tin dioxide sensitive material described in the above technical solution.
[0050] In the present invention, the double-layer membrane structure gas sensor is preferably a planar structure.
[0051] In the present invention, the thickness of the Na-type X molecular sieve cover layer is preferably 50 to 400 μm, more preferably 50 to 200 μm.
[0052] In the present invention, the thickness of the palladium-doped tin dioxide sensitive material is preferably 50 to 400 nm, more preferably 50 to 200 nm.
[0053] In the present invention, the test electrode and the heating electrode are preferably gold electrodes independently; the width of the gold electrode is preferably 0.5 to 2 mm, more preferably 0.5 to 1 mm; the distance between the two gold electrodes is preferably 0.3 to 3 mm, more preferably 0.5 to 2 mm. In the present invention, a platinum wire is preferably led out from the test electrode; the length of the platinum wire is preferably 0.5 to 1.5 cm, more preferably 1 to 1.5 cm.
[0054] In the present invention, the substrate is preferably one of a ceramic substrate, a glass substrate and a silicon substrate, and is more preferably a ceramic substrate; the ceramic substrate is preferably an Al2O3 planar ceramic substrate; the size of the substrate is preferably 0.3~1×0.9~3cm, and is more preferably 0.5~1×1.5~3cm, and the thickness is preferably 0.1~0.5mm, and is more preferably 0.2~0.4mm.
[0055] In the present invention, the heating electrode is preferably a symmetrical L-shaped gold heating electrode, and the heating plate is preferably a constant temperature heating plate.
[0056] The present invention also provides a method for preparing the double-layer membrane structure gas sensor described in the above technical solution, comprising the following steps:
[0057] A test electrode is arranged on one side of the substrate, and a heating electrode and a heating plate are sequentially stacked on the other side;
[0058] Applying a dispersion of a palladium-doped tin dioxide sensitive material to the test electrode and an uncovered area of the substrate on the side where the test electrode is provided, to obtain a palladium-doped tin dioxide sensitive material layer on the surface of the substrate and the test electrode;
[0059] The Na-type X molecular sieve dispersion is printed onto the surface of the palladium-doped tin dioxide sensitive material layer, and the double-layer membrane structure gas sensor is obtained after aging.
[0060] In the present invention, the substrate is preferably subjected to plasma hydrophilic treatment before use.
[0061] In the present invention, the palladium-doped tin dioxide sensitive material dispersion is preferably obtained by dispersing a Pd@SnO2 sensitive material and a solvent; the solvent is preferably isopropanol, ethanol or water, more preferably isopropanol; the solid-liquid ratio of the Pd@SnO2 sensitive material and the solvent is preferably 0.05-0.2g:0.2-1mL, more preferably 0.05-0.15g:0.3-0.5mL; the dispersion is preferably ultrasonic dispersion, and the time is preferably 10-20min.
[0062] In the present invention, the coating method is preferably drop coating, scraping coating or spin coating, more preferably drop coating; the drop coating is preferably dried; the drying temperature is preferably 100 to 200° C., and the drying time is preferably 30 to 50 minutes. In the present invention, the coating and drying times are independently 1 to 6 times, more preferably 2 to 5 times.
[0063] In the present invention, the Na-type X molecular sieve dispersion is preferably obtained by mixing the Na-type X molecular sieve and a solvent; the solvent is preferably isopropanol, ethanol or ethylene glycol, more preferably isopropanol; the solid-liquid ratio of the Na-type X molecular sieve and the solvent is preferably 0.01-0.10 g:0.2-1.0 mL, more preferably 0.01-0.05 g:0.2-0.5 mL; the mixing is preferably grinding mixing; the mixing temperature is preferably room temperature, and the mixing time is preferably 0.1-0.2 h.
[0064] In the present invention, the printing is preferably screen printing; the printing is preferably followed by drying; the drying temperature is preferably room temperature, and the drying time is preferably 2 to 6 hours.
[0065] In the present invention, the aging temperature is preferably 100-300° C., more preferably 200-300° C., and the aging time is preferably 3-4 days.
[0066] The present invention also provides the application of the double-layer membrane structure gas sensor or the double-layer membrane structure gas sensor prepared by the preparation method described in the above technical solution in H2 or CO detection.
[0067] In the present invention, when the double-layer membrane structure gas sensor is preferably used for hydrogen detection, the working principle is preferably:
[0068] When the double-layer membrane structure gas sensor of the present invention is placed in the air, oxygen molecules are adsorbed on the sensor surface and ionized by electrons from the conduction band of the sensitive material of the double-layer membrane (Pd@SnO2 membrane and Na-type X molecular sieve membrane) to form oxygen anions (O - or 2- ), in this process, O2 acts as an electron acceptor to reduce the electron concentration of the sensor and increase the resistance. When the sensor contacts H2 gas at a certain suitable temperature, the H2 gas molecules will react with the oxygen anions adsorbed on the sensor surface. The reaction formulas are Formula I and Formula II, causing the electrons captured by the oxygen anions to be released back into the conduction band of the Pd@SnO2 sensitive material, thereby reducing the measured resistance. The change in material resistivity is converted into an electrical signal by the sensor and received by the measuring end, thereby achieving the purpose of detecting H2.
[0069] H2+O(adsorption) - →H2O+e - Formula I;
[0070] H2+O(adsorption) 2- →H2O+2e - Formula II.
[0071] That is, the DC resistance R between the two gold electrodes is measured by the resistance meter when the resistance of the sensor is basically stable in air and H2 gas of different concentrations. a and R g , the sensitivity of the sensor at different concentrations is calculated as S = R a / R g , and then establish the "concentration and sensitivity relationship curve"; then use the resistance meter to measure the DC resistance between the two gold electrodes in the unknown concentration atmosphere, and use S = R a / R g By calculating the sensor sensitivity value at this concentration, the H2 gas concentration can be calculated using the "concentration-sensitivity relationship curve".
[0072] In order to further illustrate the present invention, the palladium-doped tin dioxide sensitive material and its preparation method, the double-layer membrane structure gas sensor and its preparation method and application provided by the present invention are described in detail below in combination with the drawings and examples, but they should not be understood as limiting the scope of protection of the present invention.
[0073] Example 1
[0074] Dissolve 0.8765g SnCl4·5H2O in 25mL deionized water, and dissolve 0.9883g NH4HCO3 in 125mL deionized water. Gradually mix the two solutions and react at 200rpm and 25℃ for 0.5h. Centrifuge the reaction product 5 times to obtain a white SnO2 precursor solution.
[0075] The SnO2 precursor solution is mixed with 20 times the mass of deionized water to obtain a SnO2 mixed solution; the pH value of the SnO2 mixed solution is adjusted to 10.5 with 28% ammonia water under stirring to obtain a tin hydroxide hydrosol; the tin hydroxide hydrosol is transferred to a stainless steel autoclave lined with polytetrafluoroethylene, and hydrothermally heated at 200°C for 3h to obtain a SnO2 gel;
[0076] After the SnO2 gel was ultrasonically treated for 10 min, 0.0025 g PdCl2 was added, and the mixture was stirred at 200 rpm and 25 °C for 1 h. 0.0025 g sodium borohydride was added, and the mixture was stirred for 2 h for reduction treatment. The obtained reduction treatment product was centrifuged 5 times, washed and freeze-dried to obtain Pd@SnO2 sensitive material.
[0077] 0.2 g of Pd@SnO2 sensitive material was mixed with 0.5 mL of isopropanol and ultrasonicated for 20 min to obtain a Pd@SnO2 dispersion.
[0078] Place the Al2O3 planar ceramic substrate (size 0.3×0.3cm, thickness 0.25mm) after plasma hydrophilic treatment on a flat table, use a pipette to drop 20μL of the above Pd@SnO2 dispersion on the upper surface of the Al2O3 planar ceramic substrate (the side of the interdigitated Au test electrode on the upper surface), so that the Pd@SnO2 dispersion completely infiltrates the upper surface of the ceramic substrate, dry it at 100℃ for 50min, repeat the above drop coating and drying treatment twice, and obtain a planar device with a Pd@SnO2 sensitive material layer;
[0079] 0.05 g of Na-type X molecular sieve nanoparticles and 0.5 mL of isopropanol were mixed and ground at room temperature for 0.2 h to obtain a Na-type X molecular sieve dispersion;
[0080] A 100 μm thick Na-type X molecular sieve slurry was printed on the surface of the planar Pd@SnO2 nanofilm using a screen printing process and dried at room temperature for 6 h. The resulting device was then soldered to a hexagonal base using a wire pad and aged in a working environment at 100°C for 3 days to obtain a double-layer membrane (SP2+NA-X type) structured gas sensor.
[0081] Figure 1 Schematic diagram of the structure of the double-layer membrane structure gas sensor obtained in Example 1 of the present invention, wherein the double-layer membrane structure gas sensor substrate is taken as a reference, (a) is a schematic diagram of the upper surface structure of the double-layer membrane structure gas sensor substrate, including a substrate 1, a test electrode 2, a platinum wire 3, a Pd@SnO2 sensitive material layer 4, and a Na-type X molecular sieve layer 5; (b) is a schematic diagram of the lower surface structure of the double-layer membrane structure gas sensor substrate, including a heating electrode 6 and a constant temperature heating plate 7.
[0082] Figure 2 The SEM images of the Pd@SnO2 sensitive material obtained in Example 1 of the present invention, wherein (a) is the SEM image of the Pd@SnO2 sensitive material when the size is 2 μm; (b) is the SEM image of the Pd@SnO2 sensitive material when the size is 1 μm; Figure 2 It can be seen that the nanoparticle Pd@SnO2 sensitive material has good film formation and the surface of the film is relatively rough, which increases the surface area of the sensitive material and is conducive to the adsorption of H2 gas molecules.
[0083] Figure 3 The XRD spectra of the Pd@SnO2 sensitive material and the Na-type X molecular sieve obtained in Example 1 of the present invention; wherein (a) is the XRD spectrum of the Pd@SnO2 sensitive material, and (b) is the XRD spectrum of the Na-type X molecular sieve, which proves that the present invention successfully synthesizes the Pd@SnO2 sensitive material.
[0084] Comparative Example 1
[0085] Dissolve 0.8765g SnCl4·5H2O in 25mL deionized water, and dissolve 0.9883g NH4HCO3 in 125mL deionized water. Gradually mix the two solutions and react at 200rpm and 25℃ for 0.5h. Centrifuge the reaction product 5 times to obtain a white SnO2 precursor solution.
[0086] The SnO2 precursor solution is mixed with 20 times the mass of deionized water to obtain a SnO2 solution; the pH value of the SnO2 solution is adjusted to 10.5 with 28% ammonia water under stirring to obtain a tin hydroxide hydrosol; the tin hydroxide hydrosol is transferred to a stainless steel autoclave lined with polytetrafluoroethylene, and hydrothermally heated at 200°C for 3 hours to obtain a SnO2 gel;
[0087] 0.2 g SnO2 gel and 0.5 mL isopropanol were mixed and ultrasonicated for 20 min to obtain SnO2 solution;
[0088] The Al2O3 planar ceramic substrate (size 0.3×0.3cm, thickness 0.25mm) after plasma hydrophilic treatment was placed on a flat table, and 20μL of the above SnO2 solution was dripped on the upper surface of the Al2O3 planar ceramic substrate (the side of the interdigitated Au test electrode on the upper surface) using a pipette to allow the SnO2 solution to completely infiltrate the upper surface of the ceramic substrate. The substrate was dried at 100°C for 50min, and the above dripping and drying treatments were repeated twice. The resulting device was then soldered to a hexagonal base using a wire pad and aged in a working environment at 100°C for 3d to obtain a single-layer film (SP0 type) structured gas sensor.
[0089] Comparative Example 2
[0090] Dissolve 0.8765g SnCl4·5H2O in 25mL deionized water, and dissolve 0.9883g NH4HCO3 in 125mL deionized water. Gradually mix the two solutions and react at 200rpm and 25℃ for 0.5h. Centrifuge the reaction product 5 times to obtain a white SnO2 precursor solution.
[0091] The SnO2 precursor solution is mixed with 20 times the mass of deionized water to obtain a SnO2 solution; the pH value of the SnO2 solution is adjusted to 10.5 with 28% ammonia water under stirring to obtain a tin hydroxide hydrosol; the tin hydroxide hydrosol is transferred to a stainless steel autoclave lined with polytetrafluoroethylene, and hydrothermally heated at 200°C for 3 hours to obtain a SnO2 gel;
[0092] After the SnO2 gel was ultrasonically treated for 10 min, 0.0025 g PdCl2 was added, and the mixture was stirred at 200 rpm and 25 °C for 1 h. 0.0025 g sodium borohydride was added, and the mixture was stirred for 2 h for reduction treatment. The obtained reduction treatment product was centrifuged 5 times, washed and freeze-dried to obtain Pd@SnO2 sensitive material.
[0093] 0.2 g of Pd@SnO2 sensitive material was mixed with 0.5 mL of isopropanol and ultrasonicated for 20 min to obtain a Pd@SnO2 dispersion.
[0094] The Al2O3 planar ceramic substrate (size 0.3×0.3cm, thickness 0.25mm) after plasma hydrophilic treatment was placed on a flat table, and 20μL of the above Pd@SnO2 dispersion was dripped on the upper surface of the Al2O3 planar ceramic substrate (the side of the interdigitated Au test electrode on the upper surface) using a pipette to allow the Pd@SnO2 dispersion to completely infiltrate the upper surface of the ceramic substrate. The substrate was dried at 100°C for 50min, and the above dripping and drying treatments were repeated twice. The resulting device was then soldered to a hexagonal base using a wire pad and aged in a working environment at 100°C for 3d to obtain a single-layer membrane structure (SP2 type) gas sensor.
[0095] Test Case
[0096] Figure 4 The response sensitivity curves of the gas sensors obtained in Example 1 and Comparative Examples 1-2 of the present invention under different temperature conditions are shown in FIG. Figure 4 It can be seen that the H2 gas sensor (SP0 type) based on the single-layer film structure of Pd@SnO2 nanoparticles in comparative example 1 has the lowest sensitivity, with the maximum sensitivity of 4.2 at 253°C; the H2 gas sensor (SP2 type) based on the single-layer film structure of Pd@SnO2 nanoparticles in comparative example 2 has a greatly improved sensitivity than (SP0 type), with the maximum sensitivity of 12.8 at 253°C; the H2 gas sensor (SP2+NA-X type) based on the double-layer film structure of nanoparticles in example 1 has a maximum sensitivity of 7.5 at 253°C.
[0097] Figure 5 The graphs are the response resistance curves of the gas sensors obtained in Example 1 and Comparative Example 1 to different concentrations of H2. Figure 5 It can be seen that when the environmental component of the gas sensor changes from air to H2, the resistance of the gas sensor drops instantly, and as the concentration of the detected gas H2 increases, the resistance change of the gas sensor becomes more obvious, that is, as the concentration of H2 increases, the sensitivity increases (and the functional relationship between the sensor sensitivity and the H2 concentration is listed in Figure 8), the lower limit of H2 concentration that can be detected by the SP2+NA-X type gas sensor prepared in Example 1 of the present invention is 3ppm, and the sensitivity is 1.2, while the detection lower limit of the SP0 type gas sensor in Comparative Example 1 is higher, which is 30ppm.
[0098] Figure 6 The response sensitivity curves of the gas sensors obtained in Example 1 and Comparative Example 1 of the present invention under different H2 concentration conditions are shown in FIG. Figure 6 It can be seen that as the H2 concentration increases, the sensitivity increases, and in low concentration (5-300ppm) and high concentration (300-1500ppm) H2 gases, the sensitivity of the SP2+NA-X gas sensor prepared in Example 1 approximately presents different linear relationships with changes in concentration.
[0099] Figure 7 The resistance change curve of the gold electrodes of the gas sensor obtained in Example 1 of the present invention after 6 cycles of 300ppm H2 gas testing is shown in FIG. Figure 7 It can be seen that the sensitivity of the SP2+NA-X type H2 gas sensor with a double-layer membrane structure prepared in the embodiment of the present invention is basically the same in multiple tests, and the device is relatively stable.
[0100] Figure 8 The response sensitivity curves of the gas sensors obtained in Example 1 and Comparative Example 2 of the present invention under different humidity conditions are shown in FIG. Figure 8 It can be seen that as the humidity continues to increase, the response of the H2 gas sensor (SP2 type) based on the nanoparticle single-layer membrane structure in comparative example 2 to 300ppm of H2 drops from 16.8 (25%RH) to 6.0 (80%RH), a decrease of 64.3%, and the baseline resistance drops from 250MΩ to 76MΩ, a decrease of 69.6%; while the response of the H2 gas sensor (SP2+NA-X type) based on the nanoparticle double-layer membrane structure to 300ppm of H2 drops from 7.3 (25%RH) to 5.1 (80%RH), a decrease of only 30.1%, and the baseline resistance drops from 56MΩ to 23MΩ, a decrease of 58.9%. This shows that the Na-type X molecular sieve layer structure provided in Example 1 of the present invention can effectively block the influence of water vapor on the Pd@SnO2 sensitive material layer, improve the moisture resistance of the device, and the equivalent resistance of the double-layer membrane is lower than that of the single-layer membrane device due to the parallel connection.
[0101] Fig. 9 The stability test curve of the gas sensor obtained in Example 1 of the present invention to 300ppm H2 at 253°C is shown in FIG. Fig. 9It can be seen that over a period of 11 days, the fluctuation range of the response of the double-layer membrane structure SP2+NA-X type H2 sensor prepared in Example 1 of the present invention was 5.0 to 7.5, which basically remained within a stable range. This shows that the double-layer membrane structure SP2+NA-X type sensor has excellent long-term stability.
[0102] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A method for preparing a palladium-doped tin dioxide sensitive material, characterized in that: The following steps are involved: The SnO2 gel, the palladium source and the reducing agent are mixed and subjected to reduction treatment to obtain the palladium-doped tin dioxide sensitive material.
2. The preparation method according to claim 1, characterized in that: The preparation method of the SnO2 gel comprises the following steps: Providing a SnO2 precursor solution, wherein the SnO2 precursor solution comprises a tin source, an alkali source and water; the pH value of the SnO2 precursor solution is 9 to 11; The SnO2 precursor solution is subjected to hydrothermal treatment to obtain the SnO2 gel.
3. The preparation method according to claim 2, characterized in that: The tin source includes one or more of tin salts, tin oxides and tin hydroxides; The alkaline source includes one or more of a weak acid and weak base salt, a strong base and a weak base.
4. The preparation method according to claim 1, characterized in that: The palladium source includes one or more of a palladium salt, a palladium oxide and palladium hydroxide.
5. The preparation method according to any one of claims 1 to 4, characterized in that: The mass ratio of the tin source to the alkali source is 1-5:1-3; The mass ratio of the tin source, the palladium source and the reducing agent is 100-500:1-3:1-5.
6. The preparation method according to claim 1, characterized in that: The temperature of the reduction treatment is 5 to 50° C., and the time is 1 to 5 hours; the reduction treatment is carried out under ultraviolet light conditions.
7. The palladium-doped tin dioxide sensitive material prepared by the preparation method according to any one of claims 1 to 6, characterized in that: The invention comprises tin dioxide and palladium particles doped on the surface of the tin dioxide.
8. A double-layer membrane structure gas sensor, characterized in that: The invention comprises a substrate, wherein a test electrode is arranged on one side of the substrate, and a heating electrode and a heating plate are sequentially stacked on the other side of the substrate; a palladium-doped tin dioxide sensitive material layer and a Na-type X molecular sieve covering layer are sequentially stacked on the surface of the test electrode and the surface of the substrate not covered by the test electrode; the palladium-doped tin dioxide sensitive material layer is formed by the palladium-doped tin dioxide sensitive material according to claim 7.
9. The method for preparing the double-layer membrane structure gas sensor according to claim 8, characterized in that: The following steps are involved: A test electrode is arranged on one side of the substrate, and a heating electrode and a heating plate are sequentially stacked on the other side; Applying a palladium-doped tin dioxide sensitive material dispersion to the test electrode and an uncovered area on the side of the substrate where the test electrode is provided, to obtain a palladium-doped tin dioxide sensitive material layer on the surface of the substrate and the test electrode; The Na-type X molecular sieve dispersion is printed onto the surface of the palladium-doped tin dioxide sensitive material layer, and the double-layer membrane structure gas sensor is obtained after aging.
10. Use of the double-layer membrane structure gas sensor according to claim 8 or the double-layer membrane structure gas sensor prepared by the preparation method according to claim 9 in H2 or CO detection.